Pemanfaatan Model Think Talk Write Berbantu Media Gambar Terhadap Keterampilan Menulis di Kelas V SDN Purwosari 01 - Afif Zaenal Arifin; Nur Fajrie; Sri Surachmi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Common problems that EFL learners face when writing are lack of vocabulary, limited understanding of grammar, and generating ideas. An alternative teaching strategy that will help them overcome this problem is the Think-Boli-Write (TTW) strategy. The purpose of this study was to confirm whether the use of the TTW strategy combined with audio-visual media had a significant effect on students' descriptive writing skills. This study uses qualitative and quantitative data. Quantitative data was taken from the results of the pretest and posttest for all cycles. Qualitative data will be used to compare the results before and after the study. They were recorded through observation, interviews and questionnaires. Based on the discussion and conclusions, a think-talk-write strategy is recommended to improve writing skills. These results indicate that the TTW strategy combined with audio-visual media improves students' descriptive writing skills; for it to be an effective strategy for English teachers in teaching descriptive writing.